Ontogenetic stages of Oulenziella bakeri (Hughes) (Acari: Winterschmidtiidae) - Fan, Qing-Hai; Li, Dong-Mei; George, Sherly (Zootaxa, 2020)
The ontogenetic stages of mite family Winterschmidtiidae are rarely studied. Here we provide detailed descriptions and illustrations of all developmental stages of Oulenziella bakeri (Hughes). A comparison of the idiosomal and leg chaetotaxy of all stages are presented. New data on hosts and distribution of O. bakeri are provided.